Augustine's inner dialogue the philosophical soliloquy in late antiquity. - Stock, Brian (Cambridge Cambridge university press, 2010)
"Augustine's philosophy of life involves reviewing one's past and exercises for self-improvement. Centuries after Plato and before Freud he invented a 'spiritual exercise' in which every man and woman is able, through memory, to reconstruct and reinterpret life's aims. Brian Stock examines Augustine's unique way of blending literary and philosophical themes. He proposes a new interpretation of Augustine's early writings, establishing how the philosophical soliloquy (soliloquium) has emerged as a mode of inquiry and how it relates to problems of self-existence and self-history. The book also provides clear analysis of inner dialogue and discourse and how, as inner dialogue complements and finally replaces outer dialogue, a style of thinking emerges, arising from ancient sources and a religious attitude indebted to Judeo-Christian tradition"--
1. Toward inner dialogue -- 2. Soliloquy and self-existence -- 3. Order and freedom -- 4. Narrative.
Keywords: Augustine, -- Saint, Bishop of Hippo; Monologue; Self; Soliloquy; Spiritual exercises